The Social Effects of Native Title Recognition, Translation, Coexistence - R. Smith, Benjamin (Research Monograph, 2007)
The papers in this collection reflect on the various social effects of native title. In particular, the authors consider the ways in which the implementation of the Native Title Act 1993 (Cwlth), and the native title process for which this Act legislates, allow for the recognition and translation of Aboriginal law and custom, and facilitate particular kinds of coexistence between Aboriginal title holders and other Australians. In so doing, the authors seek to extend the debate on native title beyond questions of practice and towards an improved understanding of the effects of native title on the social lives of Indigenous Australians and on Australian society more generally. These attempts to grapple with the effects of native title have, in part, been impelled by Indigenous people's complaints about the Act and the native title process. Since the Act was passed, many Indigenous Australians have become increasingly unhappy with both the strength and forms of recognition afforded to traditional law and custom under the Act, as well as the with socially disruptive effects of the native title process. In particular, as several of the papers in this collection demonstrate, there is widespread discomfort with the transformative effects of recognition within the native title process, effects which can then affect other aspects of Indigenous lives.